Outcome of Femoral Shaft Fracture Fixation with Titanium Elastic Nailing System in Pediatric Group of Patients with Clinical and Radiological Evaluation (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Very frequent and common paediatric orthopaedic emergency is fracture of shaft of femur. Traction and casting were the standard common practice for all femoral shaft fractures in paediatric group. Titanium Elastic Nailing System (TENS) is, now a days, a common practice for treating these fractures. In last twenty years, this fixation showed rapid union and early mobilization and have gained a general popularity.Objective: To evaluate clinical and radiological outcome of titanium elastic nailing system for displaced femoral shaft fractures in paediatric patients.Methods: This retrospective study was conducted in Orthopaedic Centre, CMH (Combined Military Hospital) Dhaka from January 2020 to December 2022. A total of 52 cases (34 boys, 18 girls), aged 6-14 years were fixed with TENS. Two nails of proper and equal diameter were used for each case. Plaster was used postoperatively upto soft tissue healing and stitch off (2 weeks postoperatively). Outcomes were assessed on the basis of Flynn et al scoring system.Results: The results of the 52 cases were included in our study. Each fracture achieved complete healing at a mean of 9.1 (Range: 8-10) weeks. 44 fractures needed closed reduction and 8 needed open reduction. Nail entry site skin irritation was recorded as minor complication in 9 patients. 78.85% got excellent result and 21.15% got satisfactory result.Conclusion: TENS has been increasingly popularized as a treatment option for paediatric shaft femur fracture over the last twenty years. It permits early mobilization and ambulation. Higher satisfaction with shorter hospital stay can be achieved with TENS. It also provides translational, angular and rotational stability to the fracture. Length can be well-achieved as well.JAFMC Bangladesh, Vol 21, No 1 (June) 2025:19-23